Pendaftaran Tanah Yang Tidak Memiliki Alas Hak Melalui Pendaftaran Tanah Sistematis Lengkap - Novida Rolianika Sitompul (Inovasi Pratama Internasional. Ltd, 2022)
The mechanism for registering PTSL for land that does not have welding rights is with a replacement letter for title in the form of PSPFBT to facilitate the acceleration of land registration by no longer requiring the land owner to attach a title certificate in the form of a Land Certificate, but only by being proven by PSPFBT The strength of physical and juridical data on the process of registering land rights in South Tapanuli based on the Minister of Agrarian and Spatial Planning of the Republic of Indonesia Number 6 of 2018 concerning PTSL is to provide legal certainty for land owners which gives a sense of security to the owner. Physical data and juridical data are evidence in the eyes of the law regarding the ownership of Rights to a piece of Land to be certified. Proof of physical data based on juridical data provided by the applicant where later the juridical data adjustment will be carried out by checking in the field, and the process of resolving land rights disputes on a plot of land registered by two people in Gianyar Regency based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning of the Republic of Indonesia Number 6 of 2018 Settlement of disputes that can be resolved through non-litigation, problem solving without going through legal channels, namely by calling the two parties concerned to the BPN office for deliberation, if in mediation there are no problems, they will not take the court route.